2000
DOI: 10.1046/j.1365-8711.2000.t01-1-03600.x
|View full text |Cite
|
Sign up to set email alerts
|

Extreme ultraviolet emission lines of Ni xii in laboratory and solar spectra

Abstract: A B S T R A C TWavelengths for emission lines arising from 3s 2 3p 5 ±3s3p 6 and 3s 2 3p 5 ±3s 2 3p 4 3d transitions in Ni xii have been measured in extreme ultraviolet spectra of the Joint European Torus (JET) tokamak. The 3s 2 3p 5 2 P 1/2 ±3s 2 3p 4 ( 3 P)3d 2 D 3/2 line is found to lie at 152X90^0X02 AY a significant improvement over the previous experimental determination of 152X95^0X5 AX This new wavelength is in good agreement with a solar identification at 152X84^0X06 AY confirming the presence of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Surprisingly, Sugar et al (1992) does not list this transition. Keenan et al (2000) reported observations with the Joint European Torus (JET) tokamak, and a wavelength of 152.90 Å for this line. However, we note that the profile of this line in the JET spectra looks asymmetric and the spectrometer used had a medium resolution of 0.2 Å.…”
Section: A Discussion On Level Energies and Line Identificationsmentioning
confidence: 94%
See 1 more Smart Citation
“…Surprisingly, Sugar et al (1992) does not list this transition. Keenan et al (2000) reported observations with the Joint European Torus (JET) tokamak, and a wavelength of 152.90 Å for this line. However, we note that the profile of this line in the JET spectra looks asymmetric and the spectrometer used had a medium resolution of 0.2 Å.…”
Section: A Discussion On Level Energies and Line Identificationsmentioning
confidence: 94%
“…These lines have similar intensities, and would be blended in most medium-resolution spectra, including the solar one of Malinovsky & Heroux (1973), and the JET tokamak (Keenan et al 2000;Mattioli et al 2004). We have re-measured the wavelength of the line observed in the Malinovsky & Heroux (1973) spectrum, obtaining a value of 152.80 ± 0.10 Å, i.e.…”
Section: A Discussion On Level Energies and Line Identificationsmentioning
confidence: 99%
“…This is illustrated in figures 1 and 2, where we show X‐ray spectra of helium‐like S xv (S 14+ ) from the Joint European Torus (JET) tokamak, and the Solar Maximum Mission (SMM) satellite, respectively (Harra‐Murnion et al 1996). For many years tokamak spectra have helped our understanding of solar observations, and vice‐versa, via for example line identifications at ultraviolet and X‐ray wavelengths (Harra‐Murnion et al 1996, Keenan et al 2000).…”
Section: Collisionally Dominated Plasmasmentioning
confidence: 99%